Detection and adequacy evaluation of erythrocyte glutathione transferase on levels of circulating toxins in hemodialysis patients. (3rd July 2016) - Yin, Rui; Qiu, Hui; Zuo, Huaiyun; Cui, Min; Zhai, Nailiang; Zheng, Hongguang; Zhang, Dewei; Huo, Ping; Hong, Min
Abstract: To explore detection and adequacy evaluation of erythrocyte glutathione S transferase (GST) on levels of circulating toxins in hemodialysis patients in Qinhuangdao region in China, this study divided 84 cases of long-term, end-stage hemodialysis patients into 2 groups: one group of 33 cases of adequate hemodialysis (spKt/V ≥ 1.3) and another group of 51 cases of inadequate hemodialysis (spKt/V < 1.3), according to the urea index value of the unit chamber model (spKt/V). Another 50 cases of subjects found healthy by a physical examination were taken as the control group, and the differences in the related clinical and biochemical indexes of the 3 groups were compared and analyzed. The levels of GST, creatinine, high sensitivity C-reactive protein (hs-CRP), transferrin saturation (TSAT), parathyroid hormone (PTH), interleukin-2, 6, 8 (IL-2, 6, 8) and tumor necrosis factor-a (TNF-a) in the hemodialysis group were significantly higher than those in the control group ( P < 0.05), and GST, IL-2, 6, 8, and TNF-a levels in the inadequate hemodialysis group were significantly higher than in the adequate hemodialysis group ( P < 0.05). Pearson's relevant analysis showed that the levels of GST and spKt/V, IL-2, IL-6, IL-8, and TNF-a have a positive correlation ( P < 0.05), and they have no correlation with levels of creatinine, hs-CRP, TSAT, and PHT ( P > 0.05). There were 23 patients with levels of spKt/V ≥ 1.3 after adjusting the dialysis solution for 51 cases of inadequate hemodialysis patients, and the GST level after the adjustment was significantly lower than that before the adjustment, but still higher than that in the adequate dialysis group. This concludes that the maintenance of hemodialysis in patients has certain relevance on spKt/V and associated inflammatory factors. Through the study, it can be determined that GST can effectively respond to adequate hemodialysis, which has a guiding significance on adjusting the blood dialysis solution in clinical practice.